OsWRKY74, a WRKY transcription factor, modulates tolerance to phosphate starvation in rice - Dai, Xiaoyan; Wang, Yuanyuan; Zhang, Wen-Hao (Journal of experimental botany, 2016)
The WRKY transcription factor family has 109 members in the rice genome, and has been reported to be involved in the regulation of biotic and abiotic stress in plants. Here, we demonstrated that a rice OsWRKY74 belonging to group III of the WRKY transcription factor family was involved in tolerance to phosphate (Pi) starvation. OsWRKY74 was localized in the nucleus and mainly expressed in roots and leaves. Overexpression of OsWRKY74 significantly enhanced tolerance to Pi starvation, whereas transgenic lines with down-regulation of OsWRKY74 were sensitive to Pi starvation. Root and shoot biomass, and phosphorus (P) concentration in rice OsWRKY74-overexpressing plants were ~16% higher than those of wild-type (WT) plants in Pi-deficient hydroponic solution. In soil pot experiments, >24% increases in tiller number, grain weight and P concentration were observed in rice OsWRKY74-overexpressing plants compared to WT plants when grown in P-deficient medium. Furthermore, Pi starvation-induced changes in root system architecture were more profound in OsWRKY74-overexpressing plants than in WT plants. Expression patterns of a number of Pi-responsive genes were altered in the OsWRKY74-overexpressing and RNA interference lines. In addition, OsWRKY74 may also be involved in the response to deficiencies in iron (Fe) and nitrogen (N) as well as cold stress in rice. In Pi-deficient conditions, OsWRKY74-overexpressing plants exhibited greater accumulation of Fe and up-regulation of the cold-responsive genes than WT plants. These findings highlight the role of OsWRKY74 in modulation of Pi homeostasis and potential crosstalk between P starvation and Fe starvation, and cold stress in rice.